If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -8(2x + -1) = 27 Reorder the terms: 3 + -8(-1 + 2x) = 27 3 + (-1 * -8 + 2x * -8) = 27 3 + (8 + -16x) = 27 Combine like terms: 3 + 8 = 11 11 + -16x = 27 Solving 11 + -16x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -16x = 27 + -11 Combine like terms: 11 + -11 = 0 0 + -16x = 27 + -11 -16x = 27 + -11 Combine like terms: 27 + -11 = 16 -16x = 16 Divide each side by '-16'. x = -1 Simplifying x = -1
| 7+13=1 | | (a-bi)(a+i)=0 | | 7x+5-2x+8= | | -9=u-6 | | 4a+6a+8b-5b= | | 3x+7=15-12x | | -3w-(-9)=12 | | P(t)=5t^2+12t+2 | | z/3.5=4 | | 47-11=36 | | 2(12.5-4x)+2x=11.5 | | 9-16y^2=0 | | 42/0.2 | | 5(7a-8)=-320 | | 12z=168 | | 2(12.5-4x)+2y=11.5 | | 4y+2.6y=36 | | 2x+7=x+7+x | | 3x-2sin(x)+7=0 | | (a-bi)(3+5i)=0 | | 9x^3-6x^2-6x+4=0 | | 2(w+3)-8w-1= | | 5x+14=4+3x | | 7(b-4)=-84 | | 3z+20=(-55) | | x-x*.17=24070 | | 7x-4+2x=5 | | n-16=21 | | 8(2n+6)=112 | | 8.304/16 | | 4x+10-6+4=20 | | 2/5x=6/35 |